Social Deficits and Cerebellar Degeneration in Purkinje Cell Scn8a Knockout Mice - Yang, Xiaofan; Yin, Hongqiang; Wang, Xiaojing; Sun, Yueqing; Bian, Xianli; Zhang, Gaorui; Li, Anning; Cao, Aihua; Li, Baomin; Ebrahimi-Fakhari, Darius; Yang, Zhuo; Meisler, Miriam H.; et al. (Frontiers in Molecular Neuroscience, 2022)
Mutations in the SCN8A gene encoding the voltage-gated sodium channel α-subunit Nav1. 6 have been reported in individuals with epilepsy, intellectual disability and features of autism spectrum disorder. SCN8A is widely expressed in the central nervous system, including the cerebellum. Cerebellar dysfunction has been implicated in autism spectrum disorder. We investigated conditional Scn8a knockout mice under C57BL/6J strain background that specifically lack Scn8a expression in cerebellar Purkinje cells (Scn8aflox/flox, L7Cre+ mice). Cerebellar morphology was analyzed by immunohistochemistry and MR imaging. Mice were subjected to a battery of behavioral tests including the accelerating rotarod, open field, elevated plus maze, light-dark transition box, three chambers, male-female interaction, social olfaction, and water T-maze tests. Patch clamp recordings were used to evaluate evoked action potentials in Purkinje cells. Behavioral phenotyping demonstrated that Scn8aflox/flox, L7Cre+ mice have impaired social interaction, motor learning and reversal learning as well as increased repetitive behavior and anxiety-like behaviors. By 5 months of age, Scn8aflox/flox, L7Cre+ mice began to exhibit cerebellar Purkinje cell loss and reduced molecular thickness. At 9 months of age, Scn8aflox/flox, L7Cre+ mice exhibited decreased cerebellar size and a reduced number of cerebellar Purkinje cells more profoundly, with evidence of additional neurodegeneration in the molecular layer and deep cerebellar nuclei. Purkinje cells in Scn8aflox/flox, L7Cre+ mice exhibited reduced repetitive firing. Taken together, our experiments indicated that loss of Scn8a expression in cerebellar Purkinje cells leads to cerebellar degeneration and several ASD-related behaviors. Our study demonstrated the specific contribution of loss of Scn8a in cerebellar Purkinje cells to behavioral deficits characteristic of ASD. However, it should be noted that our observed effects reported here are specific to the C57BL/6 genome type.